The Saga of Academic Autonomy in Slovenia (1919–1999) - Pavel Zgaga (Center for Educational Policy Studies Journal)
This article examines the concept of academic autonomy within the 'Yugoslav model' of higher education as a peripheral system characterised by an eclectic mix of elements from different systems, resulting in mutations with unique features during its development. The hitherto under-researched history of this higher education model has by no means been uniform or linear; because of this complexity, the focus here is limited to the case of Slovenia but considers the broader context. The focus is on the understanding, legislation, and (non-)implementation of academic autonomy as articulated between 1945 and 1991. The concept was inherited: it was never used in the legislation of federal socialist Yugoslavia yet was used in political and public debates. Our analysis relates these debates to the rapidly changing legislation and the broader socio-political context. Although the 'Yugoslav model' has vanished, its traces and ashes, including old contradictions and dilemmas, remain partly present in the higher education systems of independent states that emerged on the territory of the former federation. The principle that knowledge of the past is the key to understanding the present and approaching the future is confirmed in this case as well.